“Effect of valerenic acid on neuroinflammation in a MPTP-induced mouse model of Parkinson’s disease” - Rodríguez-Cruz, Alfredo (IBRO Rep, 2019)
Parkinson´s disease is the most important neuromotor pathology due to the prominent loss of dopaminergic neurons in the substantia nigra pars compacta. There is an inherent deficiency of dopamine in Parkinson´s disease, which is aggravated when neuroinflammatory processes are present. Several biomolecules are interesting candidates for the regulation of inflammation and possible neuroprotection, such as valerenic acid, one of the main components of Valeriana officinalis. A 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine hydrochloride (MPTP)-induced mouse model of Parkinson's disease was developed to evaluate the motor effects of valerenic acid. The evaluation was carried out with four tests (an invert screen test for muscle strength, cross beam test, open field mobility test and lifting on hind legs test). Subsequently, the neuroinflammatory process was evaluated through ELISA of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α and IFN-γ). The decreases in the inflammatory and neurodegenerative processes were evaluated by Western blot and immunohistochemistry analyses of the tissues, which included an evaluation of the tyrosine hydroxylase and GFAP proteins. Finally, the predicted mechanism of action of valerenic acid was supported by molecular docking calculations with the 5-HT(5A) receptor. The results indicate that the use of valerenic acid as a co-treatment decreases the neuroinflammation in Parkinson's disease induced by MPTP and provides evidence of a decrease in the evaluated pro-inflammatory cytokines and in the amount of GFAP in the mesencephalic area. Valerenic acid prevents neuroinflammation in a Parkinson's disease mouse model, which might reflect the neuroprotection of dopaminergic neurons with the recovery of motor ability.